1988
DOI: 10.1111/j.1365-2923.1988.tb00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Literature and medicine: a short course for medical students

Abstract: A course on literature and medicine for medical students is described. A wide range of books, plays and poems were used with medical and non-medical themes. Students enjoyed the course and particularly welcomed the non-medical components. The staff learned at least as much as the students. Several book lists were developed with input from the students. Such a course might have a part to play in several parts of the medical course, such as in the teaching of ethics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 5 publications
0
38
1
5
Order By: Relevance
“…As such small group narrative skills teaching requires large numbers of clinical teaching faculty who themselves need training, we designed a faculty development workshop for Osler Fellows. While there are some evidence in the literature of the impact of narrative medicine courses on medical students and residents (Radwany & Adelson, 1987;Calman et al, 1988;Marshall & O'Keefe, 1995), we were not able to find evidence on how learning was assessed following a faculty development intervention in the teaching of narrative-based skills. While many questions about narrative medicine remain unresolved (e.g.…”
Section: Practice Pointscontrasting
confidence: 41%
“…As such small group narrative skills teaching requires large numbers of clinical teaching faculty who themselves need training, we designed a faculty development workshop for Osler Fellows. While there are some evidence in the literature of the impact of narrative medicine courses on medical students and residents (Radwany & Adelson, 1987;Calman et al, 1988;Marshall & O'Keefe, 1995), we were not able to find evidence on how learning was assessed following a faculty development intervention in the teaching of narrative-based skills. While many questions about narrative medicine remain unresolved (e.g.…”
Section: Practice Pointscontrasting
confidence: 41%
“…The aims of the course were to introduce the students to literature in its broadest sense, so they could learn about life by reading of the views, insights and feelings of others, and to encourage them to examine their own attitudes and prejudices. 20 We read poems and extracts from medically relevant literature and discussed them in groups with the tutors. The evaluation suggested that 80% of the students felt the course aims had been met.…”
Section: Voluntary Coursementioning
confidence: 99%
“…Outcome studies of literature and medicine courses, relying on postcourse student evaluations, questionnaires, and faculty member assessments, reveal that such programs improve students' understanding of patients' experiences, their relationships with patients, and their functioning in clinical situations. [12][13][14] Within the more general scientific literature, writing about challenging or traumatic experiences has been shown to have health and psychological benefits in multiple studies including those in new mothers, victims of crime, and college freshmen. 15 Writing about prior trauma boosted immune response to hepatitis B vaccinations in a subgroup of medical students.…”
Section: Research Into Narrative Medicinementioning
confidence: 99%